‎‌The‌‎ ‎‌effect‌‎ ‎‌of‌‎ ‎‌eight‌‎ ‎‌weeks‌‎ ‎‌of‌‎ ‎‌perceptual‌‎-‎‌motor‌‎ ‎‌exercises‌‎ ‎‌on‌‎ ‎‌executive‌‎ ‎‌functions‌‎ ‎‌and‌‎ ‎‌the‌‎ ‎‌development‌‎ ‎‌of‌‎ ‎‌fundamental‌‎ ‎‌motor‌‎ ‎‌skills‌‎ ‎‌in‌‎ ‎‌children‌‎ ‎‌with‌‎ ‎‌intellectual‌‎ ‎‌disabilities‌‎ - Yones‏‎ Anbari‏‎; ‎‏Farzad Mohammadi; ‎‏Negar Salehi‏‎ ‎‏Mobarakeh (فصلنامه ابن سینا, 2024)
‎‏Background‏‎ ‎‏and‏‎ ‎‏aims‏‎: ‎‏Children‏‎ ‎‏with‏‎ ‎‏intellectual‏‎ ‎‏disabilities‏‎ ‎‏often‏‎ ‎‏experience‏‎ ‎‏deficits‏‎ ‎‏in‏‎ ‎‏executive‏‎ ‎‏functions‏‎ ‎‏and‏‎ ‎‏motor‏‎ ‎‏skills.‏‎ ‎‏This‏‎ ‎‏study‏‎ ‎‏aimed‏‎ ‎‏to‏‎ ‎‏investigate‏‎ ‎‏the‏‎ ‎‏impact‏‎ ‎‏of‏‎ ‎‏perceptual‏‎-‎‏motor‏‎ ‎‏exercises‏‎ ‎‏on‏‎ ‎‏improving‏‎ ‎‏both‏‎ ‎‏executive‏‎ ‎‏functions‏‎ ‎‏and‏‎ ‎‏the‏‎ ‎‏development‏‎ ‎‏of‏‎ ‎‏fundamental‏‎ ‎‏motor‏‎ ‎‏skills‏‎ ‎‏in‏‎ ‎‏children‏‎ ‎‏with‏‎ ‎‏intellectual‏‎ ‎‏disabilities.‏‎ ‎‏Methods‏‎: ‎‏This‏‎ ‎‏quasi‏‎-‎‏experimental‏‎ ‎‏study‏‎ ‎‏utilized‏‎ ‎‏a‏‎ ‎‏pre‏‎- ‎‏and‏‎ ‎‏post‏‎-‎‏test‏‎ ‎‏design‏‎ ‎‏with‏‎ ‎‏a‏‎ ‎‏control‏‎ ‎‏group.‏‎ ‎‏Twenty‏‎ ‎‏children‏‎ ‎‏with‏‎ ‎‏intellectual‏‎ ‎‏disabilities‏‎, ‎‏aged‏‎ ‎‏7‏‎ ‎‏to‏‎ ‎‏10‏‎ ‎‏years‏‎, ‎‏from‏‎ ‎‏exceptional‏‎ ‎‏schools‏‎ ‎‏in‏‎ ‎‏Abdanan‏‎ ‎‏City‏‎, ‎‏were‏‎ ‎‏randomly‏‎ ‎‏assigned‏‎ ‎‏to‏‎ ‎‏two‏‎ ‎‏homogeneous‏‎ ‎‏groups‏‎ (‎‏intervention‏‎ ‎‏and‏‎ ‎‏control‏‎) ‎‏based‏‎ ‎‏on‏‎ ‎‏age‏‎, ‎‏weight‏‎, ‎‏height‏‎, ‎‏and‏‎ ‎‏IQ.‏‎ ‎‏The‏‎ ‎‏Development‏‎ ‎‏of‏‎ ‎‏fundamental‏‎ ‎‏motor‏‎ ‎‏skills‏‎ ‎‏was‏‎ ‎‏assessed‏‎ ‎‏using‏‎ ‎‏the‏‎ ‎‏TGMD‏‎-‎‏3‏‎ ‎‏test‏‎, ‎‏while‏‎ ‎‏the‏‎ ‎‏Conners‏‎ ‎‏Neuropsychological‏‎ ‎‏Test‏‎ ‎‏Questionnaire‏‎ ‎‏evaluated‏‎ ‎‏neuropsychological‏‎ ‎‏skills‏‎ ‎‏in‏‎ ‎‏both‏‎ ‎‏groups‏‎ ‎‏during‏‎ ‎‏the‏‎ ‎‏pre‏‎- ‎‏and‏‎ ‎‏post‏‎-‎‏test‏‎ ‎‏phases.‏‎ ‎‏The‏‎ ‎‏experimental‏‎ ‎‏group‏‎ ‎‏participated‏‎ ‎‏in‏‎ ‎‏perceptual‏‎-‎‏motor‏‎ ‎‏exercises‏‎ ‎‏consisting‏‎ ‎‏of‏‎ ‎‏two‏‎ ‎‏45‏‎-‎‏minute‏‎ ‎‏sessions‏‎ ‎‏per‏‎ ‎‏week‏‎ ‎‏for‏‎ ‎‏eight‏‎ ‎‏weeks‏‎, ‎‏while‏‎ ‎‏the‏‎ ‎‏control‏‎ ‎‏group‏‎ ‎‏continued‏‎ ‎‏their‏‎ ‎‏regular‏‎ ‎‏daily‏‎ ‎‏activities.‏‎ ‎‏Results‏‎: ‎‏The‏‎ ‎‏perceptual‏‎-‎‏motor‏‎ ‎‏exercises‏‎ ‎‏significantly‏‎ ‎‏improved‏‎ ‎‏the‏‎ ‎‏development‏‎ ‎‏of‏‎ ‎‏fundamental‏‎ ‎‏motor‏‎ ‎‏skills‏‎, ‎‏as‏‎ ‎‏evidenced‏‎ ‎‏by‏‎ ‎‏enhancements‏‎ ‎‏in‏‎ ‎‏the‏‎ ‎‏locomotor‏‎ ‎‏and‏‎ ‎‏ball‏‎ ‎‏skills‏‎ ‎‏subscales‏‎ ‎‏of‏‎ ‎‏the‏‎ ‎‏TGMD‏‎-‎‏3‏‎ ‎‏test‏‎ (‎‏p<0.05‏‎)‎‏.‏‎ ‎‏Furthermore‏‎, ‎‏there‏‎ ‎‏were‏‎ ‎‏significant‏‎ ‎‏improvements‏‎ ‎‏in‏‎ ‎‏executive‏‎ ‎‏functions‏‎, ‎‏particularly‏‎ ‎‏in‏‎ ‎‏problem‏‎-‎‏solving‏‎ ‎‏and‏‎ ‎‏planning‏‎, ‎‏emotional‏‎ ‎‏and‏‎ ‎‏behavioral‏‎ ‎‏organization‏‎, ‎‏and‏‎ ‎‏overall‏‎ ‎‏executive‏‎ ‎‏function‏‎ ‎‏scores‏‎ (‎‏p<0.05‏‎)‎‏.‏‎ ‎‏Conclusion‏‎: ‎‏Perceptual‏‎-‎‏motor‏‎ ‎‏exercises‏‎ ‎‏effectively‏‎ ‎‏enhance‏‎ ‎‏executive‏‎ ‎‏functions‏‎ ‎‏and‏‎ ‎‏fundamental‏‎ ‎‏motor‏‎ ‎‏skills‏‎ ‎‏in‏‎ ‎‏children‏‎ ‎‏with‏‎ ‎‏intellectual‏‎ ‎‏disabilities.‏‎ ‎‏It‏‎ ‎‏is‏‎ ‎‏recommended‏‎ ‎‏that‏‎ ‎‏educators‏‎ ‎‏and‏‎ ‎‏occupational‏‎ ‎‏therapists‏‎ ‎‏incorporate‏‎ ‎‏these‏‎ ‎‏exercises‏‎, ‎‏with‏‎ ‎‏appropriate‏‎ ‎‏precautions.‏‎